2021
DOI: 10.1038/s41598-021-91795-y
|View full text |Cite
|
Sign up to set email alerts
|

The homogenous alternative to biomineralization: Zn- and Mn-rich materials enable sharp organismal “tools” that reduce force requirements

Abstract: We measured hardness, modulus of elasticity, and, for the first time, loss tangent, energy of fracture, abrasion resistance, and impact resistance of zinc- and manganese-enriched materials from fangs, stings and other “tools” of an ant, spider, scorpion and nereid worm. The mechanical properties of the Zn- and Mn-materials tended to cluster together between plain and biomineralized “tool” materials, with the hardness reaching, and most abrasion resistance values exceeding, those of calcified salmon teeth and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 105 publications
(124 reference statements)
2
39
0
Order By: Relevance
“…stercoraria and St. calcitrans to have higher amounts of inorganic elements than species of other feeding habits, but this was not observed (Table 3). Metal ions and other inorganic elements are known to enhance the material properties of insect cuticles, particularly on structures that rasp or pierce hard substrates [35][36][37][38]. Here, the studied cuticular elements were in low concentrations (mostly <1%) for all species.…”
Section: Prestomal Teeth Materials Properties In Relation To Feeding ...mentioning
confidence: 77%
“…stercoraria and St. calcitrans to have higher amounts of inorganic elements than species of other feeding habits, but this was not observed (Table 3). Metal ions and other inorganic elements are known to enhance the material properties of insect cuticles, particularly on structures that rasp or pierce hard substrates [35][36][37][38]. Here, the studied cuticular elements were in low concentrations (mostly <1%) for all species.…”
Section: Prestomal Teeth Materials Properties In Relation To Feeding ...mentioning
confidence: 77%
“…the penetration of surfaces as well as the durability and wear resistance of the tool 19 . From this point of view, a recent work showed that the actions of penetrating surfaces as well as resisting wear and tear are aided by metals inclusion in the cuticle 12 . This is in accordance with a previous study, which showed the presence of metal ions in the fangs of the spiders that act as reinforcing elements 12 , 14 .…”
Section: Discussionmentioning
confidence: 99%
“…From this point of view, a recent work showed that the actions of penetrating surfaces as well as resisting wear and tear are aided by metals inclusion in the cuticle 12 . This is in accordance with a previous study, which showed the presence of metal ions in the fangs of the spiders that act as reinforcing elements 12 , 14 . Moreover, the different microstructural organization of the cuticle body parts (legs, prosoma, outer layer, and inner layer of the fangs) has been related to the polymorphic forms differentiated into their crystal structure 48 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations